TMOD-11. MODELING AND TARGETING KIAA1549-BRAF DRIVEN CNS TUMORS. (23rd April 2019) - Kannan, Ram; Cook, Peter; Yao, Zhan; Lee, Jieun; Mastroleo, Chiara; Ogrodowski, Paul; Rosen, Neal; Benezra, Robert; Ventura, Andrea
Abstract: Low-grade gliomas account for ~30% of primary central nervous system tumors arising in children. Although LGGs grow slowly, inoperable tumors can lead to morbidity and premature death. The most common oncogenic event observed in nearly 70% of cases of Pilocytic astrocytomas (PA) and diffuse leptomeningeal glioneuronal tumors (DLGT)—is a recurrent tandem duplication on chromosome 7. This complex rearrangement results in the fusion of BRAF C-Terminus comprising of the kinase domain with KIAA1549 N-Terminus, an uncharacterized gene. Apart from creating this fusion, the entire region between KIAA1549 and BRAF comprising of 17 protein coding genes is duplicated. Currently, there are no accurate preclinical models for KIAA1549-BRAF duplication which has hindered targeted therapy for this class of pediatric brain tumors. Although cDNA overexpression of KIAA1549-BRAF has been shown to activate the MAPK pathway, in vivo models overexpressing the fusion protein lack the physiological features of either PA or DLGT. Our hypothesis in this project is that generating the entire tandem duplication event in addition to the Kiaa1549-Braf fusion is necessary for modeling the patho-physiological characteristics of the pediatric brain tumors. We have employed CRISPR based somatic genome editing to generate the tandem duplication of Kiaa1549-Braf in p53 -/- adult neural stem cells ex-vivo, which results in brain tumors predominantly growing in the subarachnoid/leptomeningeal space and displays histopathological features of human DLGT. Further, we have shown that the Kiaa1549-Braf driven tumor lines can be inhibited by next generation Braf dimer inhibitors. In summary, we have developed a new preclinical model for Kiaa1549-Braf driven brain cancer and demonstrated efficacy against a new preclinical Braf inhibitor.